If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8p + -1(1 + -3p) = -89 8p + (1 * -1 + -3p * -1) = -89 8p + (-1 + 3p) = -89 Reorder the terms: -1 + 8p + 3p = -89 Combine like terms: 8p + 3p = 11p -1 + 11p = -89 Solving -1 + 11p = -89 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 11p = -89 + 1 Combine like terms: -1 + 1 = 0 0 + 11p = -89 + 1 11p = -89 + 1 Combine like terms: -89 + 1 = -88 11p = -88 Divide each side by '11'. p = -8 Simplifying p = -8
| R-7=-3 | | 5x-4=52-9y | | 6m-5= | | (5/2*4) | | 70-(5x+8)=40 | | 1/3x2=16 | | M^2=-49+14m | | N+4-6n+3= | | (2x+8)=116 | | J+184.06=317.91 | | (x^3-3x+1)-(x^3+7-12x)= | | r^2-16r+39=0 | | 2x^2-4=8x | | -34+37+17=x | | 14-2x+4x=14 | | 5x^3-17x^2-12x=0 | | -16-7x=-30 | | -7mr(12m-7r+5)=0 | | -4(-5-b)=0.3(b+16) | | y=6(4(3^1/2)) | | 4(2x-4)-x+5=79 | | -5x+5(-x+3)=115 | | -9z^2+9z-2=0 | | 6(3x+4)+2x-4=100 | | 7-(-6)-8+3=x | | (2y)(4y^3)+(3y^2)(5y^2)=0 | | -5y+2x=10x+15 | | -14.16r=433.44 | | 4-x^2=16 | | X/5=85/30 | | 6=2/5m | | 4y-6=1.5x+4 |